Role of Lipid Accumulation and Inflammation in Atherosclerosis: Focus on Molecular and Cellular Mechanisms - Malekmohammad, Khojasteh; Bezsonov, Evgeny E.; Rafieian-Kopaei, Mahmoud (Frontiers in Cardiovascular Medicine, 2021)
Atherosclerosis is a chronic lipid-driven and maladaptive inflammatory disease of arterial intima. It is characterized by the dysfunction of lipid homeostasis and signaling pathways that control the inflammation. This article reviews the role of inflammation and lipid accumulation, especially low-density lipoprotein (LDL), in the pathogenesis of atherosclerosis, with more emphasis on cellular mechanisms. Furthermore, this review will briefly highlight the role of medicinal plants, long non-coding RNA (lncRNA), and microRNAs in the pathophysiology, treatment, and prevention of atherosclerosis. The comprehensive information in this review article was obtained from noteworthy scientific databases, including Web of Science, PubMed, Science Direct, Scopus, and Google Scholar. Lipid homeostasis at various levels, including receptor-mediated uptake, synthesis, storage, metabolism, efflux, and its impairments are important for development of atherosclerosis. The major source of cholesterol and lipid accumulation in the arterial wall is proatherogenic modified low-density lipoprotein (mLDL). Modified lipoproteins, such as ox-LDL and LDL binding with proteoglycans of the extracellular matrix in the intima of blood vessels, cause aggregation of lipoprotein particles, endothelial damage, leukocyte recruitment, foam cell formation, and inflammation. Inflammation is the key contributor to atherosclerosis and participates in all phases of atherosclerosis. Also, several studies have shown that microRNAs and lncRNAs have appeared as key regulators of several physiological and pathophysiological processes in atherosclerosis, including regulation of HDL biogenesis, cholesterol efflux, lipid metabolism, regulating of smooth muscle proliferation, and controlling of inflammation. Thus, both lipid homeostasis and the inflammatory immune response are closely linked, and their cellular and molecular pathways interact with each other.